2015
DOI: 10.1007/s00726-015-2049-3
|View full text |Cite
|
Sign up to set email alerts
|

Protein function prediction using guilty by association from interaction networks

Abstract: Protein function prediction from sequence using the Gene Ontology (GO) classification is useful in many biological problems. It has recently attracted increasing interest, thanks in part to the Critical Assessment of Function Annotation (CAFA) challenge. In this paper, we introduce Guilty by Association on STRING (GAS), a tool to predict protein function exploiting protein-protein interaction networks without sequence similarity. The assumption is that whenever a protein interacts with other proteins, it is pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…where the direct neighbours of a gene of interest are assumed to be implicated in similar processes [14], to machine learning (ML) algorithms designed to learn from the features of the network to make more useful biological predictions (e.g. [15]).…”
Section: Introductionmentioning
confidence: 99%
“…where the direct neighbours of a gene of interest are assumed to be implicated in similar processes [14], to machine learning (ML) algorithms designed to learn from the features of the network to make more useful biological predictions (e.g. [15]).…”
Section: Introductionmentioning
confidence: 99%
“…Using these constructed attribute features and annotated proteins, a classifier can be trained first and then be used to predict function annotations for unannotated proteins. On the other hand, graph-based approaches [6][7][8] assume that the closely related proteins (or genes) share similar functional annotations on the basis of network structure information. In [9], protein interactions were measured by several computational approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In CAFA2, GO-FDR [12], one of the best 47 performing systems on all three GO ontologies, calculates the probability of a protein 48 being associated with a target GO term, using predictions from the PSI-BLAST tool. 49 Recently, You et al [13] suggested an approach based on an ensemble of logistic 50 regression models which, resulted in the best overall performance among the 51 participating teams in the CAFA3 challenge. For each GO term, a set of three logistic 52 regression models are independently trained based on structural information from 53 InterPro [14], biophysical attributes from ProFET [15] and amino acid n-gram features.…”
mentioning
confidence: 99%
“…Firstly, features derived 386 from sequences related in other ways than solely through homology, e.g. through 387 co-expression or binding, can be potentially beneficial especially for the prediction of 388 biological processes, as demonstrated for instance by Piovesan et al [51] and Kulmanov 389 et al [18]. Of the three GO ontologies, biological process currently exhibits the lowest 390 absolute performance, and therefore is the most impactful target for further 391 development.…”
mentioning
confidence: 99%